DNA directed self-assembly of shape-controlled hydrogels - Qi, Hao (2013)
Using DNA as programmable, sequence specific ‘glues’, shape-controlled hydrogel units are self-assembled into prescribed structures. Here we report that aggregates are produced using hydrogel cubes with edge length ranging from 30 micrometers to 1 millimeter, demonstrating assembly across scales. In a simple one-pot agitation reaction, 25 dimers are constructed in parallel from 50 distinct hydrogel cube species, demonstrating highly multiplexed assembly. Using hydrogel cuboids displaying face-specific DNA glues, diverse structures are achieved in aqueous and in interfacial agitation systems. These include dimers, extended chains, and open network structures in an aqueous system; and dimers, chains of fixed length, T-junctions, and square shapes in the interfacial system, demonstrating the versatility of the assembly system.